Cadrage exquis: Reframing Jean-Jacques Beineix's Diva. Issue 2 (May 2015) - HAINGE, GREG
Abstract : In the first instance, this article revisits the critical reception of Jean-Jacques Beineix's Diva at the time of its release and the abundant critical commentary it has received since. It then goes on to propose a new reading of Diva that does not follow either the damning critiques of it as an empty and apolitical exercice de style or those that, taking their cue from Benjamin, see the film as a historically-situated commentary on a specific aspect of the political or ideological context in which the film was made. Against these readings, I suggest that through thematic and formal means, and in particular through the use of the soundtrack, Diva can be read as a metacommentary on the cinema more generally and one which, what is more, deliberately and positively distances the cinematic from the political. It is suggested, finally, that the cadrage in operation here explicitly, but in the cinema more generally, thus has much in common with the Surrealist cadavre exquis, since it involves the combination of diverse elements within a single work in such a way that the logic that binds those elements together can remain operational only within the artwork.